Reversible Cortical Blindness as a Prominent Manifestation of Cerebral Embolism due to Infective Endocarditis - Georgios P. Kranidiotis; Alexandra N. Gougoutsi; Theodoros A. Retsas; Maria I. Anastasiou-Nana (Case Reports in Medicine)
Introduction. Infective endocarditis in the left heart may be complicated by stroke, due to embolisation from infectious valvular vegetations. Infarction of both occipital lobes, which are supplied by the posterior cerebral arteries, is infrequent, and is the cause of cortical blindness from lesion of the visual cortex. Cortical blindness is characterized by intact pupillary reflexes, a normal fundoscopy, and, rarely, denial of visual loss. Case Presentation. We report the case of a 58-year-old woman, recipient of a mechanical aortic valve, who presented with fever, multiple organ dysfunction, and cortical blindness. Transesophageal echocardiography and blood cultures confirmed the diagnosis of infective endocarditis caused by methicillin-sensitive Staphylococcus aureus. Computed tomography of the brain without contrast revealed the presence of infarctions in both occipital lobes. It is noteworthy that the visual loss resolved after treatment of endocarditis. Conclusions. A stroke occurring in a patient presenting with fever and a history of valvular heart disease strongly suggests the presence of infective endocarditis. Bilateral thromboembolic infarcts of the occipital lobes cause cortical blindness, that can resolve after treatment of endocarditis.